IMPLEMENTASI SISTEM PENGENDALIAN MANAJEMEN DALAM MENINGKATKAN PRODUKTIVITAS DAN MENGATASI HAMBATAN BISNIS ONLINE BODY CARE PADA PT. SASTRO UTAMA MEDIA GRUP - Lilik Rahmadani; Halpiah Halpiah (Nusantara Hasana Journal, 2021)
This study entitled "Implementation of Management Control Systems in Increasing Productivity and Overcoming Barriers to Online Body Care Business at PT. Sastro Utama Media Grup “. The purpose of this study is to determine whether the implementation of the management control system has been going well or not, to know the extent of the application of the management control system at PT. Sastro Utama Media Grup to increase productivity, and 3. To find out what are the obstacles in the application of the management control system at PT. Sastro Utama Media Group. This research is a qualitative research with a descriptive approach. Data collection techniques in this study were interviews and documentation. The main informants in this study are the Owner and HRD at PT. Sastro Utama Media Grup. Data analysis techniques in this study were data reduction, data presentation, and interesting reports. The results of this study indicate that the implementation of a management control system has been implemented but has not been maximized It can be seen from some staff who are placed in divisions that do not match their backgrounds and incidents of concurrent positions, PT. Sastro Utama Media Grup does not prepare budgets that are issued either monthly or annually, obstacles in online business that are often faced are more competitive competitors and a lack of understanding of digital marketing, obstacles in the application of a management control system are not having an internal audit team and no supervision carried out by external audit, absence of management information systems, absence of accounting information systems, and the absence of an internal control system.